An Analysis of Nutrition-Relevant National Policies in South Asia Reveals a Gap in Addressing the Essential Nutrition Actions Recommended by World Health Organization (WHO). (29th May 2020) - Neupane, Sumanta; Jangid, Manita; Scott, Samuel; Nguyen, Phuong; Kim, Sunny; Menon, Purnima; Murira, Zivai; Torlesse, Harriet
Abstract: Objectives: The WHO recommends Essential Nutrition Actions (ENAs) throughout the life course to tackle malnutrition in all its forms. However, limited evidence exists on the availability of policies to support the implementation of ENAs in South Asia, a region with the highest burden of malnutrition globally. We conducted a policy analysis to assess the extent to which current policies address ENAs for adolescent girls, women, and children in South Asia. Methods: We first identified the WHO ENAs targeting non-pregnant menstruating adolescent girls (1 ENA), non-pregnant women of reproductive age (2 ENAs), pregnant women (6 ENAs), postpartum women (2 ENAs), and children aged 0–5 years (25 ENAs). We then reviewed 40 health- and nutrition-relevant national policy and program documents, strategic plans, and guidelines for health workers from Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. Using these documents, we identified policies that address the ENAs. We report the number of recommended ENAs addressed by the policies for each population group. Results: National nutrition policies exist in all eight countries. Six countries have multi-sector nutrition plans or strategy. These documents primarily guide provisions for nutrition actions in the region. Six countries have policies that address the ENA for non-pregnant menstruating adolescent girls. Only two countries have policies that address both ENAs for non-pregnant women of reproductive age. For pregnant women, three countries address four of six ENAs, but no countries address all six ENAs. Seven countries have policies that address both ENAs for postpartum women. Five countries have policies that address more than 20 of 25 ENAs for children aged 0–5 years. Conclusions: Our policy analysis identifies substantial gaps in national policies related to the ENAs among South Asian countries and gaps are more pronounced for non-pregnant women of reproductive age and for pregnant women. Policy revisions, including updating policies, implementation and financing plans, will be needed to deliver the ENAs at scale and with quality to enable the South Asian region to tackle malnutrition in all its forms. Funding Sources: Bill and Melinda Gates Foundation through DataDENT.